Behavior of Political Elite Taxpayers and Political Connections to Tax Obligations during the COVID-9 Pandemic - Megawanti Megawanti; Alimuddin; Nirwana (Jurnal Economic Resource, 2023)
This research focuses on the behavior of political elite taxpayers and their political connections during the COVID-19 pandemic. The research object is the political elite, entrepreneurs, and entrepreneurs who have connections with the political elite in Balikpapan. Using Husserl's transdental phenomenological study to gain an in-depth understanding of the behavior and meaning of tax with tax subjects using the terms "politically elite taxpayers" and "politically connected taxpayers", as a form of perspective on the other side of exploring taxpayer behavior and the meaning of tax by adding a subject to new research other than what has been done by previous researchers (e.g., WP-OP, WP-UMKM, WP-UMK). Meanwhile, it is known that 22 of the 45 political elites in the Balikpapan city legislature have business backgrounds. Even though he later left the management of the company, unless he was still registered as a director for a certain reason along with his existing political connections, it left questions about his independence from his duties as a legislative political elite and his partiality for his business or for his group. Rent-seeking opportunities, budgeting for people's welfare projects, and the distribution of donations for handling COVID-19 are things that they see for themselves to explore compliance, the meaning of taxes, and their behavior in light of the policies that they set in their company. Tax-related policies, this research only focuses on the cost of COVID-19 donations due to indications of large tax aggressiveness and indications of the legitimacy of companies and themselves as political elites with political connections. As a result of the research, based on the reduction of deep meaning found in information from informants, there is suspicion of other political elites prioritizing personal or group interests in project planning and implementation. Political elite taxpayer informants and politically connected taxpayers chose not to follow the rules for implementing the distribution of COVID-19 assistance and chose not to take existing tax facilities to reduce the company's tax burden on humanitarian grounds, and it was difficult to prepare data according to tax rules.